Innovative teaching experiences in geometry: Tracing and construction of vaults - Martín Talaverano, Rafael; Antolín Cano, Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The geometry and the architectural drawing are essential tools for the graphical expression, perhaps the most important language within the frames of the architecture and engineering. Although its importance is clear, some of the students which deal with the geometry feel that it is a quite complex and abstract signature, with no relationship with the reality, so that they are not motivated. This paper presents three teaching experiences directed to solve this problem in which a challenge is proposed: the construction of a vault or a dome. In this way, the students had to investigate and understand several geometric concepts.